The Northern Ireland Biobank: A Cancer Focused Repository of Science. (11th September 2018) - Lewis, Claire; McQuaid, Stephen; Clark, Priscilla; Murray, Paul; McGuigan, Tracey; Greene, Christine; Coulter, Bronagh; Mills, Ken; James, Jacqueline
The Northern Ireland Biobank (NIB) was established in 2011 as a joint initiative between Queen's University Belfast and Belfast Health and Social Care Trust to provide the infrastructure for the standardised collection and storage of high quality, well annotated human tissue samples, with matched bloods and bodily fluids to underpin cancer research in Northern Ireland and beyond. The NIB has been instrumental in supporting translational research locally, nationally and internationally with a number of key achievements to date. The vision of NIB is to develop an internationally recognised biobank network within Northern Ireland which collects, stores and distributes high quality, clinically annotated biospecimens for biomarker research to benefit cancer patients.